The Impact of Growth Mindset on Student Leadership in Diverse Learning Environments (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study investigates the relationship between growth mindset interventions and the development of student leadership skills in diverse educational settings. It examines how cultivating a growth mindset among students can enhance their leadership abilities, such as initiative, collaboration, and problem-solving, within and outside the classroom.